2018
DOI: 10.1158/1541-7786.mcr-18-0056
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling of Patient-matched Head and Neck Cancer Cells: A Preclinical Pipeline for Metastatic and Recurrent Disease

Abstract: : Metastases and tumor recurrence have a major prognostic impact in head and neck squamous cell carcinoma (HNSCC); however, cellular models that comprehensively characterize metastatic and recurrent HNSCC are lacking. To this end, we obtained genomic, transcriptomic, and copy number profiles of the UM-SCC cell line panel, encompassing patient-matched metastatic and recurrent cells. UM-SCC cells recapitulate the most prevalent genomic alterations described in HNSCC, featuring common TP53, PI3K, NOTCH, and Hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
5
26
0
Order By: Relevance
“…The effect of PI3Ki on proliferation was significantly enhanced when CQ was added to the treatment. We performed the same experiment with a panel of HPV-negative HNSCC cell lines harboring the most common PIK3CA alterations ( Figure 2 D), but all mutated for TP53 [ 40 , 41 , 42 , 43 , 44 ]. TP53 mutated cell lines represent 86% of HPV-negative HNSCC cases [ 3 ], and a study found TP53 mutations in 95% of metastatic HNSCC [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of PI3Ki on proliferation was significantly enhanced when CQ was added to the treatment. We performed the same experiment with a panel of HPV-negative HNSCC cell lines harboring the most common PIK3CA alterations ( Figure 2 D), but all mutated for TP53 [ 40 , 41 , 42 , 43 , 44 ]. TP53 mutated cell lines represent 86% of HPV-negative HNSCC cases [ 3 ], and a study found TP53 mutations in 95% of metastatic HNSCC [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 which shows the distributions of positive values in pairwise comparisons involving zero and a positive count. The distributions are shown for two different datasets: A transcriptomic dataset analyzed in [14] and a phosphoproteomic dataset analyzed in [Koch et al, manuscript in preparation] (see “Description of the transcriptomic data” section and “Description of the phosphoproteomic data” section for the datasets’ descriptions). To allow for easy comparison, the counts are scaled by the dataset’s median in both cases.…”
Section: Resultsmentioning
confidence: 99%
“…Description of the transcriptomic data The transcriptomic data from head and neck squamous cell carcinoma patient-derived cell lines have been originally analyzed in [14] (the authors have used edgeR for the differential expression analysis). Out of the 15 cell lines used in that study, we keep eight of them for pairwise differential expression analysis: Cell lines UM-SCC-11A, -14A, -74A, and -81A from primary tumors, and cell lines UM-SCC-11B, -14B, -74B, and -81B from recurrent tumors.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed by Nisa et al, SPRR2A played a dual role in invasion and therapeutic resistance in head and neck squamous cell carcinoma. High expression of SPRR2A in lymph node metastases was, along with the nonoropharyngeal location of the primary tumor, an independent prognostic factor for regional disease recurrence after surgery and radiotherapy [ 14 ]. In the present study, serum SPRR2A expression in patients with GC, gastritis, and colorectal cancer and in healthy people was detected by ELISA.…”
Section: Discussionmentioning
confidence: 99%